2021
DOI: 10.1088/1755-1315/777/1/012008
|View full text |Cite
|
Sign up to set email alerts
|

Sex ratio, age group and length at first maturity of mackerel scad (Decapterus macarellus Cuvier, 1833) in the Southern waters of Ambon, Eastern Indonesia

Abstract: The existence of mackerel scad in Ambon waters, Moluccas Indonesia has decreased from year to year mainly due to the over exploitation. This research aimed to study the biological aspects, in particular were sex ratio, age group and length at first maturity of mackerel scad (Decapterus macarellus) from this area. Sampling was done on September 2016 to July 2017 at the southern waters of Ambon Island. Samples collected were dissected to determine their sex and their gonad maturity level then measured. Bhattacha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…The dominance of female D. kurroides in the randomly collected samples was also observed in other round scad species, such as the Decapterus russelli in Malabar Coast, India (Manojkumar 2005) and Decapterus macarellus in Ambon, Indonesia (Silooy et al 2021). The deviation from the 1:1 ratio is unlikely for most aquatic organisms, such as fishes (Khatun et al 2018).…”
Section: Discussionmentioning
confidence: 67%
“…The dominance of female D. kurroides in the randomly collected samples was also observed in other round scad species, such as the Decapterus russelli in Malabar Coast, India (Manojkumar 2005) and Decapterus macarellus in Ambon, Indonesia (Silooy et al 2021). The deviation from the 1:1 ratio is unlikely for most aquatic organisms, such as fishes (Khatun et al 2018).…”
Section: Discussionmentioning
confidence: 67%
“…To date, it has been reported that there are 11 valid species of roundscads worldwide (Froese & Pauly, 2022) and 8 of those species occur in Indonesian waters, namely D. akaadsi, D. kurroides, D. macarellus, D. macrosoma, D. maruadsi, D. muroadsi, D. russelli and D. tabl (Baweleng et al, 2018;Dahlan et al, 2015;Firdaus et al, 2020;Latumeten et al, 2019;Ongkers et al, 2016;Pattikawa et al, 2017Pattikawa et al, , 2018Purnama, 2020;Silooy et al, 2021;Umar et al, 2019). Latumeten et al (2019) in their research in Doreri Bay, Manokwari found 3 species of roundscads caught by lift net, namely D. akaadsi, D. macarellus and D. macrosoma.…”
Section: Species Compositionmentioning
confidence: 99%
“…In addition, Pattikawa et al (2018) found a total length ranging from 11.0-24.5 cm and Silooy et al (2019) reported a range of 9.0-31.9 cm for this species in the waters of Ambon Island. According to Silooy et al (2021), first matured gonads of this species at 24.9 cm (male) and 24.8 cm (female). Based on this information, it can be concluded that most of the D. macarellus sold in the traditional fish market of Langgur City are…”
Section: Size Distributionmentioning
confidence: 99%
See 1 more Smart Citation
“…The main commercial fish species caught by this fishery in deeper waters of the South China Sea are tuna (family Scombridae) and tuna‐like species and scads (dominated by Mackerel Scad Decapterus macarellus and Shortfin Scad D. macrosoma ) (Zhang et al 2016a; Su et al 2018). These fish stocks are made up of highly migratory species and are exploited by several countries around the South China Sea (Zhang et al 2016b; Tadjuddah et al 2017; Su et al 2018; Silooy et al 2021). Unfortunately, most of them have not been assessed because of a lack of data.…”
Section: Introductionmentioning
confidence: 99%